Introduction: American Game Studies - Jagoda, Patrick; Malkowski, Jennifer (American Literature, 2022)
In 2017, the American game designer Momo Pixel released the single-player, browser-based game Hair Nah. In this game, you play as Aeva, a Black woman taking trips to locations that include Osaka, Havana, and the Santa Monica Pier. As you move through levels on your journey—taking a taxi ride, traversing airport security, sitting on an airplane—you must slap away increasingly aggressive white hands that reach into the frame to touch your hair. Though Hair Nah taps into the genre of a casual button-mashing game, this interactive experience also explores the topic of microaggressions via unwanted hair touching. If you slap away enough hands on your travels, you reach a screen welcoming you to your destination with the message “YOU WIN!” but the caveat, “The game is over, but this experience isn’t. This is an issue that black women face daily. So a note to those who do it STOP THAT SHIT.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

The View from here Conversations with Gay and Lesbian Filmmakers - Hays, Matthew (Arsenal Pulp Press, 2007)
The history of gay and lesbian cinema is a storied one, and became that much larger with the recent success of Brokeback Mountain. But the history of gay and lesbian filmmakers is its own story. In The View From Here, queer directors and screenwriters speak passionately about the medium, in particular their personal experiences navi-gating the often cynical and cruel film industry. All of them offer fascinating anecdotes and ideas about cinema, and speak candidly about their attempts to combat studio apathy and demands of “the market” to create films that are entertaining, engaging, and truthful.
Pages: 1 vol. (383 p.) :
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Two-Spirit Resistance - Mcneil-Saymour, Jeffrey (Whose Land is it anyway? A Manual for Decolonization., 2017)
The publication of Whose Land Is It Anyway? A Manual for Decolonization is inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The handbook provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation
Section: 79 pages : illustrations (some color) ; 29 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé